AN EXPERIENCE WITH LEECHES IN THE AERODIGESTIVE TRACT - Akhtar, Sunarays; Haq, Inam ul (Pakistan Armed Forces Medical Journal, 2006)
The leech is a haemophagic parasite, living on occasional meals of blood obtained by attaching to fish, amphibians, and mammals. They attach to their hosts and remain there. Leech bodies are composed of 34 segments. Externally, leeches tend to have a brown and red striped design on an olive colored background (fig. 1). These organisms have two suckers, one at each end, called the anterior and posterior sucker. The posterior is mainly used for leverage while the anterior sucker, consisting of the jaw and teeth, is where the feeding takes place.Leech saliva contains a number of compounds which assist in its feeding. An anesthetic limits the sensations felt by the host (and thus reduces the chance of the host trying to detach the leech). A vasodilator causes the blood vessels near the leech to become dilated, and thus provides the leech with a better supply.  Leech saliva contains a complex protein called hirudin, which is a highly effective anticoagulant. The leech needs this to prevent blood clots (which would block its feeding) [1].